2020
DOI: 10.1182/blood-2020-134746
|View full text |Cite
|
Sign up to set email alerts
|

Complete Responses in Relapsed/Refractory Acute Myeloid Leukemia (AML) Patients on a Weekly Dosing Schedule of Vibecotamab (XmAb14045), a CD123 x CD3 T Cell-Engaging Bispecific Antibody; Initial Results of a Phase 1 Study

Abstract: Background: Blasts and leukemic stem cells of acute myeloid leukemia (AML) as well as several other hematologic malignancies express CD123, potentially providing a target for novel therapies. Vibecotamab (XmAb14045, SQZ622) is a potent bispecific antibody targeting both CD123 and CD3 that stimulates targeted T cell-mediated killing of CD123-expressing cells, regardless of T cell antigen specificity. It is a full-length immunoglobulin molecule designed to be dosed intermittently. Methods: Patient… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
30
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 57 publications
(33 citation statements)
references
References 0 publications
0
30
0
Order By: Relevance
“…Characterization of responders versus non-responders revealed responding patients harbored a lower pretherapy burden of disease and specific T-cell subtypes. No association was found between response status and CD123 target expression on AML blasts (84).…”
Section: Dual Affinity Retargeting Antibodiesmentioning
confidence: 87%
“…Characterization of responders versus non-responders revealed responding patients harbored a lower pretherapy burden of disease and specific T-cell subtypes. No association was found between response status and CD123 target expression on AML blasts (84).…”
Section: Dual Affinity Retargeting Antibodiesmentioning
confidence: 87%
“…The ORR was 15% in 54 evaluable patients who received a dose of at least 0.75 mcg/kg. The ORR increased to 26% for patients with a baseline blast count less than or equal to 25% in the bone marrow, suggesting vibecotamab might provide better efficacy in patients with low burden of disease [94].…”
Section: Antibody-based Treatmentsmentioning
confidence: 96%
“…With the addition of an Fc domain, XmAb14045 had a significantly longer half-life at 6.2 days [57]. Preliminary results from a multicenter, open-label phase 1 dose-escalation study of XmAb14045-01 (vibecotamab) in 106 patients with relapsed or refractory hematologic malignancies (104 patients with R/R AML) showed an overall response rate (ORR) of 14% (7 out of 51 patients) at the higher dose level, with two patients achieving a CR [58]. However, no patients treated with the lower dose experienced an objective response.…”
Section: Cd123mentioning
confidence: 99%
“…Notably, 58.5% of patients developed CRS with 15% of CRS events being ≥ grade 3. Correlative studies also suggested that patients with lower disease burden and specific T-cell subtypes had a higher likelihood of response, while CD123 expression on AML blasts was not associated with response [58].…”
Section: Cd123mentioning
confidence: 99%